The effect of high-intensity interval training on cognitive function in patients with substance use disorder: Study protocol for a two-armed randomized controlled trial - Haberstroh, Carolin; Weider, Siri; Flemmen, Grete; Loe, Henrik; Andersson, Helle Wessel; Hallgren, Mats; Mosti, Mats Peder (Frontiers in Sports and Active Living, 2022)
Introduction Substance use disorder (SUD) is characterized by cognitive impairment, especially executive dysfunction. Executive function is recognized as an important determinant of treatment outcome as it is associated with dropout rate, attendance to therapy and potential relapse after treatment termination. Physical activity can have beneficial effects on cognitive function, but there is still a lack of knowledge regarding potential benefits of aerobic exercise for executive function in SUD treatment. The aim of this study is to examine the effect of aerobic high-intensity interval training (HIIT) on cognitive function and the subsequent effect on treatment outcome in patients with SUD. Methods and analysis This study is a randomized controlled trial, including men and women ≥18 years with diagnosed SUD by ICD-10. The patients will be recruited from the department for inpatient treatment at Blue Cross - Lade Addiction Treatment Center, Trondheim, Norway. Participants will be randomized 1:1 into either HIIT (3x/week) + treatment as usual (TAU), or TAU alone. Study outcomes will be assessed at baseline, after eight weeks of intervention, and at 3- and 12-months follow-up. The primary outcome is to compare the change in executive function (via altered BRIEF-A score, Behavior Rating Inventory of Executive Function-Adult) measured between the two study groups after eight weeks. Secondary outcomes include mapping of cognitive function in different subgroups (e.g. type of substance, age, fitness level), collecting self-reported information about quality of life, craving, sleep quality, etc., as well as assessing compliance to TAU and long-term treatment outcome. Ethics and dissemination The project was approved by the Regional Ethical Committee and will be performed in accordance with this protocol and the Declaration of Helsinki. Written informed consent will be obtained from all participants prior to inclusion. This project will explore a novel approach to how exercise can be applied in SUD treatment, beyond the well-known effects on physical health. We expect to achieve new knowledge in regard to what extent HIIT can improve cognitive abilities and subsequent treatment outcome in SUD. Trial registration number https://www.clinicaltrials.gov/NCT05324085.